2003
DOI: 10.1149/1.1553791
|View full text |Cite
|
Sign up to set email alerts
|

The pH Response Drift of Thermally Grown Titanium Oxide Thin Films

Abstract: The pH-response drift of thermally grown oxide film on titanium electrode was investigated through Devanathen hydrogen permeation tests and open-circuit potential measurements. Thermostatic measurements using heat-treated titanium electrodes were conducted in solutions with pH being changed stepwise from pH 4 to pH 10. A numerical simulation of the pH-response drift based on a diffusion-controlled model was made using experimental values of hydrogen diffusion coefficient and oxide film concentrations as parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Hence the problem raised by Bard, Sav eant and co-workers [8][9][10] remains unsolved. Notice that Yu and Yen have recently made a similar remark in their study of Tijporous TiO 2 electrodes [17]. Notice also that in 1987, in their theoretical EIS study of a porous layer-coated RDE, Deslouis et al found [18] that D f and L can be determined separately, but c was not taken into account in their model (which amounts to taking c ¼ 1).…”
Section: Introductionmentioning
confidence: 84%
“…Hence the problem raised by Bard, Sav eant and co-workers [8][9][10] remains unsolved. Notice that Yu and Yen have recently made a similar remark in their study of Tijporous TiO 2 electrodes [17]. Notice also that in 1987, in their theoretical EIS study of a porous layer-coated RDE, Deslouis et al found [18] that D f and L can be determined separately, but c was not taken into account in their model (which amounts to taking c ¼ 1).…”
Section: Introductionmentioning
confidence: 84%
“…Hydrogen penetration into the oxide depends on a number of parameters, including the oxide's chemical composition and structure [20,29,34,35], the presence of Ti n+ interstitials and/or oxygen vacancies [36], the types of impurities and their concentration, the adsorption characteristics of the oxide surface [37], the solubility of hydrogen in the oxide, and environmental parameters, such as electrochemical potential [38] and temperature. Given these complexities and the absence of experimental data for aqueous solutions, it is difficult to predict how fast hydrogen will be transported through the oxide and what fraction of the hydrogen atoms generated on the oxide surface will reach the Ti substrate.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is a material with a large range of applications, due to its versatility (11), high refractive index, photo stability, and biocompatibility (12). These oxide thin films have been proposed for applications in sensors due to their extensive response range as a function of pH, as well as low cost and high sensitivity (13). It is largely used in biosensors applications due to good compatibility, high orientation, and high uniformity (14).…”
Section: Introductionmentioning
confidence: 99%